Surfactant and non invasive ventilation for preterm infants - Gizzi, C.; Papoff, P.; Campelli, et al., M. (Acta Biomedica Atenei Parmensis, 2012)
Mechanical ventilation, although life-saving, predisposes preterm infants to BPD. NCPAP emerged as an alternative to invasive ventilation, but it fails in about 30% of infants even when coupled with surfactant therapy. Alternative modes of non invasive ventilation are currently used in neonatology in order to prevent mechanical ventilation. Among these, Synchronized Nasal Intermittent Positive Ventilation (SNIPPV) seems to ensure better results.